Evidence for a regulatory role of Cullin-RING E3 ubiquitin ligase 7 in insulin signaling - Scheufele, Florian; Wolf, Benjamin; Kruse, Michael; Hartmann, Thomas; Lempart, Justine; Muehlich, Susanne; Pfeiffer, Andreas F.H.; Field, Loren J.; Charron, Maureen J.; Pan, Zhen Qiang; Engelhardt, Stefan; Sarikas, Antonio (Cellular Signalling, 2014)
Dysfunctional regulation of signaling pathways downstream of the insulin receptor plays a pivotal role in the pathogenesis of insulin resistance and type 2 diabetes. In this study we report both in vitro and in vivo experimental evidence for a role of Cullin-RING E3 ubiquitin ligase 7 (CRL7) in the regulation of insulin signaling and glucose homeostasis. We show that Cul7-/- mouse embryonic fibroblasts displayed enhanced AKT and Erk MAP kinase phosphorylation upon insulin stimulation. Depletion of CUL7 by RNA interference in C2C12 myotubes led to increased activation of insulin signaling pathways and cellular glucose uptake, as well as a reduced capacity of these cells to execute insulin-induced degradation of insulin receptor substrate 1 (IRS1). In vivo, heterozygosity of either Cul7 or Fbxw8, both key components of CRL7, resulted in elevated PI3 kinase/AKT activation in skeletal muscle tissue upon insulin stimulation when compared to wild-type controls. Finally, Cul7+/- or Fbxw8+/- mice exhibited enhanced insulin sensitivity and plasma glucose clearance. Collectively, our findings point to a yet unrecognized role of CRL7 in insulin-mediated control of glucose homeostasis by restraining PI3 kinase/AKT activities in skeletal muscle cells. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2024-07-10
Keywords: Cell signaling; E3 ubiquitin ligase; Insulin; Proteasome; Ubiquitin